algebra

Solve by substitution method
3x+8y=17
2x+y=14
please show step by step so i can understand better. I keep getting it wrong at the end.

  1. 👍
  2. 👎
  3. 👁
  1. Subtract 2x from both sides of 2x+y=14.

    y = 14-2x

    3x+8y=17

    Substitute 14-2x for y in second equation and solve for x. Insert that value into the first equation and solve for y. Check by inserting both values into the second equation.

    1. 👍
    2. 👎

Respond to this Question

First Name

Your Response

Similar Questions

  1. math

    Consider the sequence of steps to solve the equation: 5(x - 3) = 7x 2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3 ⇒ 3x - 30 = 0 Step 4 ⇒ 3x = 30 Step 5 ⇒ x = 10 Identify the property of equality which yields

  2. math

    10a) Simplify the expression and explain each step. 12 + 3(2y – 3) Step 1: apply distributive property Step 2: combine like terms Step 3: simplify b) Factor the expression completely. 18b – 12 What is the GCF of 18 and 12? Use

  3. math

    An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,

  4. Algebra 2

    V=df-di/tf-tf; solve for tf Please show step by step procedure so I can understand how to solve this. Many thanks.

  1. Math

    Note: Enter your answer and show all the steps that you use to solve this problem in the space provided. Solve the equation. Explain each step and identify the property used to reach each step. 0.6x + 0.8 = 1.4

  2. Math

    Note: Enter your answer and show all the steps that you use to solve this problem in the space provided. Use inverse operations to solve each equation. Explain each step and identify the property used to reach step. 19= h/3 -8

  3. math

    Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10 Which step in solving this equation is justified by the Commutative Property of Addition? Given ⇒ 2(x − 4) + 6x = 9x − 10 Step 1 ⇒ 2x − 8

  4. Algebra

    How do I solve for the elimination method: 5x + 3y= -7 and 7x - 2y =13 (step 1); 10x + 6y =-14 and 21x -6y = 39 ( step 2), 31x/31= 25/31, x= 25/31 (step 4). But after that I get lost. Can somebody help me out please.

  1. math

    What is the first step in solving the linear system {2x−3y=11 {−x+5y=−9 by the substitution method in the most efficient way? A. Solve the first equation for x. B. Solve the first equation for y. C. Solve the second equation

  2. ALGEBRA HELP

    When solving the equation, what property was used to go from step 3 to step 4? Step 1: -(2x+3= x-18 Step 2: -2x-3=x-18 Step 3: -3=3x-18 Step 4: 15=3x A)APOE B)SPOE C)MPOE D)DPOE

  3. PreCalc

    Approximate the solutions to the following equation on the interval [0,2π). Round your answer to four decimal places. sinθ=0.65 Apparently, there suppose to be two answers to this question with a comma separating​ both

  4. math

    What is the first step in solving the linear system {2x − 3y = 11 {−x + 5y = −9 by the substitution method in the most efficient way? A. Solve the first equation for x. B. Solve the first equation for y. C. Solve the second

You can view more similar questions or ask a new question.